Towards the Theory of the Naïve Art – Grgo Gamulin and the Understanding of Modernism - Mance, Ivana (Artium Quaestiones, 2019)
The article presents the theory of naïve art of the Croatian art historian Grgo Gamulin (1910–1997), which he developed in a number of texts written from early 1960s. In his theory, Gamulin tried to explain the phenomenon of naïve art on the basis of the modernist paradigm by applying the type of argumentation that is characteristic for the discourse of high-modernity. Gamulin’s postulates on the naïve can be summarised with a few basic lines of speculation. First of all, Gamulin claims that the phenomenon of the naïve was epistemologically possible only in the context of modernism, and that it should therefore be considered an equally valuable movement of contemporary art. However, in order to defend its authenticity, he began adhering to the ab ovo theory, the notion that naïve art does not arise as a cumulative result of the historical development of art, but that it ontologically precedes that development. The naïve artist, according to Gamulin, always starts from the beginning, independent of events in the art world, and immune to influences. A naïve artist is therefore necessarily authentic, or rather original: not having any role models, he develops an individual style, independently building his own visual arts language. Gamulin further posits that the visual arts language of the naïve is not based on a naive imitation of reality, or mimesis, but on an instinctive, spontaneous symbolisation of subjective experience, and as such is completely autonomous in relation to the laws of reality, i.e. it is ontologically grounded in the artist’s imagination. Finally, in an effort to explain the social significance of naïve art, Gamulin interprets the emergence of the naïve in the context of the culture of modernism as compensation – a supposedly naïve attitude to aesthetic norms, as well as an imaginarium that evokes “lost spaces of childhood,” necessarily functions as a therapeutic substitute for the alienation of art and the modern life in general. As such, Gamulin’s theory vividly testifies to the character of naïve art as a phenomenon that is constitutive of the culture of modernism, but that also reflects a number of contemporary polemics and split opinions, not only on the topic of the naïve but of modernism as a whole. The split of opinions on naïve art, especially with regard to its genesis, partly reflects the positions of the so-called conflict on the left, discussions that were taking place between the interwar period and early 1950s with the aim of defining the relationship of leftist ideology to modernism, or rather the relationship between the values of socially-critical engagement and aesthetic autonomy. The discussion on the naïve, however, experienced a certain changing of sides– Grgo Gamulin, a one-time advocate for socialist realism, began supporting naïve art and thus rose to the defence of basically liberal understanding of modernism, while former opponents of socialist realism denounced the phenomenon of the naïve as ideologically inconsistent and aesthetically doctored. In conclusion, Gamulin’s theory, as well as the entire polemic around naïve art that was taking place during the 1960s and which the theory necessarily ties in with, demonstrates the complex contextual reality of a seemingly integral modernist paradigm, illustrating the confrontation of positions that is by no means peculiar to Yugoslav society.